Children with asthma on inhaled corticosteroids managed in general practice or by hospital paediatricians: is there a difference? - Kuethe, Maarten C (Prim Care Respir J, 2010)
AIM: To investigate whether there are differences in asthma characteristics between two populations of children with moderate asthma requiring inhaled corticosteroids (ICS) who are treated in general practice or in hospital practice. PATIENTS AND METHODS: 45 children from general practice and 62 from hospital practice, diagnosed with asthma and treated with ICS, were analysed in terms of lung function parameters, asthma control (ACQ), and use of medication. RESULTS: Children in general practice did not differ significantly from those in paediatric practice with respect to mean age, lung function tests, and corrected daily dose of ICS. The median ACQ score was higher (representing poorer control) in the general practice group than in the paediatric practice group (0.67 and 0.33 respectively, p < 0.05). Fewer children (22.7%) from the general practice group than from the paediatric group (98.4%) had planned review visits (p< 0.01). Prescriptions for a combination ICS/long-acting β(2)-agonist (LABA) inhaler were 28.9% in the general practice group and 6.5% in the paediatric group (p<0.05). CONCLUSION: The hospital-based group was better controlled with less frequent use of combination therapy. Our observations stress the necessity for regular review visits for children with moderately severe asthma especially in general practice.